Prognostic impact of prior LVEF in patients with heart failure with mildly reduced ejection fraction - Schmitt, Alexander; Behnes, Michael; Weidner, Kathrin; Abumayyaleh, Mohammad S. A.; Reinhardt, Marielen; Abel, Noah; Lau, Felix; Forner, Jan; Ayoub, Mohamed; Mashayekhi, Kambis; Akın, Ibrahim; Schupp, Tobias (Clinical research in cardiology, 2024)
As there is limited evidence regarding the prognostic impact of prior left ventricular ejection fraction (LVEF) in patients with heart failure with mildly reduced ejection fraction (HFmrEF), this study investigates the prognostic impact of longitudinal changes in LVEF in patients with HFmrEF.
Gesehen am 04.09.2024